The fiscal burden of the legacy of the civil service pension systems in northern Cyprus - Altiok, Hasan U.; Jenkins, Glenn P. (Cambridge Univ Press, 2013)
This paper estimates the fiscal burden of the Pay-As-You-Go (PAYGO) civil service pension systems that were closed in 2008 to new members in North Cyprus. Estimates are made of the difference between the present values of future contributions and the future pension benefits. The future pension benefits are those received by the individuals covered through these plans for the period from 2009 to the death of the last member in the system. The estimated unfunded cost of these historical civil service pension plans is 7.3 billion euros or 276% of GDP.
Keywords: Civil service pensions; pension liabilities; implicit pension debt; pension indexing; North Cyprus